P212 Changing TB trends in west hertfordshire: what does this mean for our service?. (December 2018) - Read, N; Reeve, L; Jayaratnam, A
Abstract : Introduction and objectives: Nationally and regionally tuberculosis (TB) incidence is declining. However the West Hertfordshire (WH) TB service is treating patients in increasing numbers and of changing nationalities. This review studies the changing incidence and epidemiology of TB in WH with a view to adapting our local service to serve the needs of the changing TB patient population. Methods: Annual report data sets from the national Enhanced Tuberculosis Surveillance system (ETS), were extracted for patients within the WH TB service. 483 patients treated between 2000 and 2016 were examined. Further patient presentation data was collected from clinical records. Results: There is a demonstrable shift from 2010 for increasing numbers of patients with active TB being treated by the service, contrary to national and regional trends. The number of geographical regions patients present from is consistent, however these regions are changing with an increasing numbers from Eastern European (EE) countries and sustained numbers from South Asian countries. The average age of the EE cohort was 32, with male predominance (67%). All EE patients entered the UK pre-2015 and therefore pre-latent TB screening (LTBI). Mean time to presentation since entry to UK was 7.4 years. The majority of EE patients had pulmonary TB (78%) of which 100% were sputum smear positive. There was no multi-drug-resistant TB. Over 50% of EE patients presented via emergency care. 22.2% (2) EE patients were lost to follow up compared to the WH cohort mean of 3.7%. Conclusions: Increasing numbers of new TB cases within WH, bucks both national and regional trends. Rising numbers of EE patients provides a challenge to our service particularly with significant proportions presenting acutely and being lost to follow up. This could be due to several issues including the challenges of introducing LTBI screening in primary care, low registration rates with GPs of new entrants from high incidence countries and lack of awareness of access to NHS services. The WH TB service needs to adapt to meet the needs of this changing group, in a more focussed way and raise TB awareness, in the acute trust, primary care and community settings.